Encyclopedia of global studies - Anheier, Helmut K. 1954-; Juergensmeyer, Mark (Sage, 2012)
"The Encyclopedia of Global Studies is the reference work for the emerging field of global studies. It covers both transnational topics and intellectual approaches to the study of global themes, including: the globalization of economies and technologies; the diaspora of cultures and dispersion of peoples; the transnational aspects of social and political change; the global impact of environmental, technological and health changes; and the organizations and issues related to global civil society."-Provided by publisher.